Sujeitos iluminados: a reconstituição das experiências vividas no estúdio de Christiano Jr. - Beltramim, Fabiana (2009)
This M.A dissertation is a historical study of the photographic collection of Christiano Jr between 1864 and 1866. Most of his photographs were made in his studio, in Rio de Janeiro and sold as souvenirs, and it is one of the largest collection of photographs of the black population in Rio de Janeiro, documenting its multiple social nets in the local urban slave society. We confronted his collection with other photographies of the same period and also of the period after his departure in 1866 aiming at a comparative and relational perspective of analysis. Our aim was broadly to research the visual culture common to a society in which the social hierarchy was determined by race, trying to pursue its different significants, its uses of and its circulation of images. The photographic technique in this period was also adopted by racialist scientificism in the second half of the 19th century as a method of observation and of classification of local data of ethnographic interest